PENGUATAN NILAI-NILAI LUHUR KEARIFAN LOKAL MASYARAKAT BUGIS MELALUI PENDEKATAN BUTTERFLY EFFECT DAN RIPPLE EFFECT UNTUK PEMBENTUKAN KARAKTER GENERASI Z - Sumartan, Sumartan; Kurnia, Fakhruddin; Ayu, Ari; Arnas, Riska; Putri P, Andi Sri Kumala Putri P; Nurwafiyyah, Auliyah; Basri, Jumriah; Heady S, Muhammad G. Try; Daming, Hamdi M. (Universitas Mataram, 2025)
Globalization has had a significant impact on people's lifestyles, including diminishing the younger generation’s appreciation for the noble cultural values of local traditions, such as the Bugis culture in Sidenreng Rappang Regency. This community service program aims to identify and strengthen the noble values of the Bugis local wisdom through the Butterfly Effect and Ripple Effect approaches in shaping the character of Generation Z. Cultural values such as honesty (lempu'), intelligence (amaccang), propriety (assitinajang), resilience (agettengeng), effort (reso), and the principle of shame (siri') serve as the main foundation implemented in culturally-based educational activities. The Butterfly Effect approach involves key individuals as cultural ambassadors to spread these values through small actions that create a significant impact, while the Ripple Effect spreads positive influence continuously through community-based programs. Through intergenerational mentoring programs, folk tale competitions, traditional art performances, and culture-based skills training, the youth of Sidenreng Rappang are encouraged to apply local values in their daily lives. The results of this community service show that the application of these two approaches can enhance pride in local culture and strengthen the character of Generation Z, making them more resilient in facing the challenges of the times without losing their cultural roots